(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This article is devoted to the use of wind generator as a source of direct current to power the excitation system of autonomous synchronous machines. Synchronous motor is a converter of alternating current electrical energy entering the stator winding and direct current electrical energy entering the rotor winding into mechanical energy. There are basically two types of supply of the synchronous motor excitation system with direct current static, where the current is drawn from the motor stator and independent, where the source of direct current is a battery or DC generator. For stationary machines in mining enterprises, mainly synchronous motors are used, where it is possible to use a DC wind generator as a source to power the field winding of synchronous motors.